(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Cooperative learning has become a fundamental teaching-learning strategy for the social construction of knowledge. This methodology is ideal for preschool students in regions such as Latin America and the Caribbean, where the effects of learning poverty condition socioeconomic development. Therefore, the objective was to assess the incidence of cooperative learning in the teaching of geometry in 5-year-old students of educational preschool institutions in the three natural regions of Peru. This research was qualitative and descriptive-correlational. Two data collection instruments were applied to 78 students who served as a sample. The Spearman’s Rho was used to analyze the relationship between the variables, which confirmed the positive relationship between them; therefore, the influence of incorporating this type of learning has an impact on the logical development of children. A quality education with optimal learning strategies will lead these students in the future to a good level of performance in academic tests such as PISA.